Iodate respiration by Azoarcus sp. DN11 and its potential use for removal of radioiodine from contaminated aquifers - Sasamura, Seiya; Ohnuki, Toshihiko; Kozai, Naofumi; Amachi, Seigo (Frontiers in Microbiology, 2023)
Azoarcus sp. DN11 was previously isolated from gasoline-contaminated groundwater as an anaerobic benzene-degrading bacterium. Genome analysis of strain DN11 revealed that it contained a putative idr gene cluster (idrABP1P2), which was recently found to be involved in bacterial iodate (IO3−) respiration. In this study, we determined if strain DN11 performed iodate respiration and assessed its potential use to remove and sequester radioactive iodine (129I) from subsurface contaminated aquifers. Strain DN11 coupled acetate oxidation to iodate reduction and grew anaerobically with iodate as the sole electron acceptor. The respiratory iodate reductase (Idr) activity of strain DN11 was visualized on non-denaturing gel electrophoresis, and liquid chromatography–tandem mass spectrometry analysis of the active band suggested the involvement of IdrA, IdrP1, and IdrP2 in iodate respiration. The transcriptomic analysis also showed that idrA, idrP1, and idrP2 expression was upregulated under iodate-respiring conditions. After the growth of strain DN11 on iodate, silver-impregnated zeolite was added to the spent medium to remove iodide from the aqueous phase. In the presence of 200 μM iodate as the electron acceptor, more than 98% of iodine was successfully removed from the aqueous phase. These results suggest that strain DN11 is potentially helpful for bioaugmentation of 129I-contaminated subsurface aquifers.